Organisation of the Educational Process in Higher Art Education Institutions of Ukraine - Anna Bokshan (Pedagogical Discourse, 2024)
The article analyses the peculiarities of the development and organisation of the educational process in higher art education institutions of Ukraine at the turn of the XX-XXI centuries, taking into account the socio-political, cultural and historical, economic, material and technical, scientific factors that led to changes in the structure and content of the educational environment.In the context of study of the theoretical issues of the problem of organization the educational process in higher art education institutions of Ukraine, we examined the essentials of the fundamental concepts of the study: education, art education, fine arts education, artistic and pedagogical education, culture.It is determined that training of future specialists in higher education institutions should be provided by the implementation of a competence-based approach to professional activity. The development of a student's professionalism begins in the period of his/her studies at an educational institution, where the appropriate professional competences are formed. The effectiveness of the educational process depends on many of its components - establishing conditions for quality education, сreating motivation for personal development and self-improvement, use of various innovative technologies, etc.     It was found out that the synthesis of education and culture into an educational and cultural holistic space is based on the principle of multiculturalism. The study of the history of arts, traditional crafts, customs  and peculiarities of the development of art education in historical and ethnographic territories contributes to a deeper understanding of the cultural heritage and its impact on the modern development of Ukraine. Therefore, it is important to organise the educational process in higher art education institutions in Ukraine on the basis of  understanding the cultural heritage and its impact on the modern development of society.     Thus, the formation of professional competences of an art specialist involves the preparation of a competitive personality in the national and European labour market. Training of such specialists is based on the identity of the national art education system, with a view to the diversity of the spectrum of spiritual values. Improving the general and professional level is a practical tool for strengthening the culture of the nation through the poly-artistic education of an intellectual and creative personality.